PENERAPAN STANDAR KOMPETENSI DAN KUALIFIKASI GURU TERHADAP PENGELOLAAN PENDIDIK DAN TENAGA KEPENDIDIKAN DI TK NEGERI 2 YOGYAKARTA - Dewi Fahmi Ats-tsanny (QURROTI, 2020)
The research purposes to determine the management of educators and educational staff in TK Negeri 2 Yogyakarta and to find out whether teachers are in accordance with the competency and qualification standards set by the government. This type of research is a qualitative research that is a process of research conducted naturally and naturally in accordance with objective conditions in the field without any manipulation, as well as the type of data collected prioritizes qualitative data. Data collection techniques in this study are observation, interviews and documentation. The results of this study are the management of educators and education personnel at TK Negeri 2 Yogyakarta through recruitment and coaching. In the qualifications and competency standards of educators and education personnel determined by the government, TK Negeri 2 Yogyakarta already has qualification standards and teacher competencies consisting of pedagogical, social, personality and professional competencies.